Do housing tenure and car access predict health because they are simply markers of income or self esteem? A Scottish study. Issue 10 (October 1998) - Macintyre, S; Ellaway, A; Der, G; Ford, G; Hunt, K
Abstract : OBJECTIVE: To investigate relations between health (using a range of measures) and housing tenure or car access; and to test the hypothesis that observed relations between these asset based measures and health are simply because they are markers for income or self esteem. DESIGN: Analysis of data from second wave of data collection of West of Scotland Twenty-07 study, collected in 1991 by face to face interviews conducted by nurse interviewers. SETTING: The Central Clydeside Conurbation, in the West of Scotland. SUBJECTS: 785 people (354 men, 431 women) in their late 30s, and 718 people (358 men, 359 women) in their late 50s, participants in a longitudinal study. MEASURES: General Health Questionnaire scores, respiratory function, waist/hip ratio, number of longstanding illnesses, number of symptoms in the last month, and systolic blood pressure; household income adjusted for household size and composition; Rosenberg self esteem score; housing tenure and care access. RESULTS: On bivariate analysis, all the health measures were significantly associated with housing tenure, and all except waist/hip ratio with car access; all except waist/hip ratio were related to income, and all except systolic blood pressure were related to self esteem. In models controlling for age, sex, and their interaction, neither waist/hip ratio nor systolic blood pressure remained significantly associated with tenure or care access. Significant relations with all the remaining health measures persisted after further controlling for income or self esteem. CONCLUSIONS: Housing tenure and car access may not only be related to health because they are markers for income or psychological traits; they may also have some directly health promoting or damaging effects. More research is needed to establish mechanisms by which they may influence health, and to determine the policy implications of their association with health.